An Online, Moderated Peer-to-Peer Support Bulletin Board for Depression: User-Perceived Advantages and Disadvantages - Griffiths, Kathleen Margaret (JMIR Ment Health, 2015)
BACKGROUND: Online, peer-to-peer support groups for depression are common on the World Wide Web and there is some evidence of their effectiveness. However, little is known about the mechanisms by which Internet support groups (ISGs) might work. OBJECTIVE: This study aimed to investigate consumer perceptions of the benefits and disadvantages of online peer-to-peer support by undertaking a content analysis of the spontaneous posts on BlueBoard, a well-established, moderated, online depression bulletin board. METHODS: The research set comprised all posts on the board (n=3645) for each of 3 months selected at 4 monthly intervals over 2011. The data were analyzed using content analysis and multiple coders. RESULTS: A total of 586 relevant posts were identified, 453 (77.3%) reporting advantages and 133 (22.7%) reporting disadvantages. Positive personal change (335/453, 74.0%) and valued social interactions and support (296/453, 65.3%) emerged as perceived advantages. Other identified benefits were valued opportunities to disclose/express feelings or views (29/453, 6.4%) and advantages of the BlueBoard environment (45/453, 9.9%). Disadvantages were negative personal change (50/133, 37.6%), perceived disadvantages of board rules/moderation (42/133, 31.6%), unhelpful social interactions/contact with other members (40/133, 30.1%), and technical obstacles to using the board (14/133, 10.5%). CONCLUSIONS: Consumers value the opportunity to participate in an online mutual support group for mental health concerns. Further research is required to better understand how and if these perceived advantages translate into positive outcomes for consumers, and whether the perceived disadvantages of such boards can be addressed without compromising the safety and positive outcomes of the board.